Financial Performance of Public Enterprises of Nepal (Patan Pragya, 2021)
Public enterprises are established, owned, and managed by the government to run industrial and commercial activities. The objective of the study is to examine the financial status of Public Enterprises (PEs) of Nepal. The study assesses based on some selected profitability indicators for eleven years. One public enterprise from each sector of the total of six sectors of them was selected. Secondary data was used. The sources such as the annual reviews by the Ministry of Finance, the annual report by Nepal Rastra Bank were chosen. This is purely quantitative research. Profitability ratios such as NPR, ROCE, ROE, and OER were employed over the years in analyzing the available financial information. Mean were computed for key analysis. NAC has the highest mean on NPR followed by NOC,DDC, JEMCL, and NEA. The NAC has the best financial status among sample PEs in terms of NPR. The finding suggests that the performance of NOC recorded the highest on ROCE. This is followed by NAC, NEA, JEMCL and DDC.NOC has the highest mean on ROE followed by RBB, NAC, JEMCL, DDC, and NEA. NEA has the highest mean on OER among the sample PEs. This is followed by DDC, NOC, NAC, RBB and JEMCL. NOC has the highest performance in terms of ROCE and ROE. Similarly, NAC has the highest performance on NPR. JEMCL seems to be the highest efficiency and cost-effective in terms of OER.